The Influence of the Activities of the Rohis Extracurricular Organization on the Morals of Learners (Research in MAN Kiarakuda, Ciawi District, Tasikmalaya Regency) - Ilham Arif Pebriansyah; Tatang Muh Nasir; Arief Agus Triansyah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The problem that arises is whether there is a positive influence from the activities of the Rohis extracurricular organization on the morals of students at MAN Kiarakuda, Ciawi District, Tasikmalaya Regency? This study aims to determine the effect of the activities of the Rohis extracurricular organization on the morals of students at MAN Kiarakuda, Ciawi District, Tasikmalaya Regency. With this aim, this research can be useful for the development of religious knowledge and prayer through intermediaries and its benefits for one of the morals of students. The method used in this research is descriptive method through a quantitative approach, namely research that seeks to reveal the current conditions/conditions by considering the past through questionnaires, interviews, as well as observation and processing of the figures obtained from the research. Based on the results of data processing, it was found that the activities of the Rohis MAN Ciawi extracurricular organization were classified as low. This is indicated by the average value (